Typical response of CD14++CD16– monocyte to knee synovial derived mediators as a key target to overcome the onset and progression of osteoarthritis - Saffery, Nik Syazana Izyan; Genasan, Krishnamurithy; Chan, Chee Ken; Ayob, Khairul Anwar; Teo, Seow Hui; Al-Fayyadh, Mohamed Zubair Mohamed; Othman, Iekhsan; Abidin, Syafiq Asnawi Zainal; Raman, Murali Malliga; Raghavendran, Hanumantha Rao Balaji; Kamarul, Tunku (Frontiers in Medicine, 2022)
Objective: Synovitis with an increased infiltration of immune cells is observed in osteoarthritis (OA). Given the inflammatory condition of synovitis, we explored the protein profile of OA synovium (OAS) and its effect on circulating monocytes activation, migration and functional commitments. Methods: Knee-synovium was acquired from end-stage OA (N=8) and trauma patients (Trauma baseline control: TBC, N=8) for characterisation using H&E histology, IHC (iNOS), LCMS-QTOF and MALDI-imaging. Response of peripheral blood monocytes to OAS conditioned-media (OACM) was observed using transwell (n=6). The migrated cells were captured in SEM, quantified using phase-contrast microphotographs and its activation receptors (CCR2, CXCR2, CX3CR1 and CD11b), Pro-inflammatory genes and phagocytic potential were studied using flow cytometry, gene expression array/qPCR and latex beads (LB) phagocytosis assay, respectively. Results: The Venn-diagram displayed 119 typical proteins in OAS, while 55 proteins in TBCS. The STRING protein network analysis indicated distinctive links between proteins and gene ontology (GO) revealed proteins associated with leukocyte mediated immunity in OAS as compared to TBC. The MALDI-imaging showed typical localised proteins at 2234.97, 2522.61, 2627.21, 3329.50 and 3539.69 m/z and IHC confirmed pro-inflammatory iNOS expression in OA synovium. CD14++CD16- classical monocytes significantly migrated in OACM and expressed CCR2, CXCR2 and CD11b receptors, TNFRSF11A, MAPK1, S100A8, HSPB1, ITGAL, NFATC1, IL13RA1, CD93, IL-1β, TNF-α and MYD88 genes and increased LB uptake as compared to SFM. Conclusion: Our findings suggest that the differential protein profile of OA synovium and the classical monocytes migrated, activated and functionally committed in response to these mediators could be of therapeutic advantage.